Effect of Fe and Al based coagulants and disinfectants on polyethylene microplastics removal in coagulation process through response surface methodology - Fatemeh Tabatabaei; Roya Mafigholami; Hamid Moghimi; Sanaz Khoramipoor (Water Science and Technology, 2023)
Microplastic (MP) pollution has been rising as a threatening risk and recently has appealed to the attention of more researchers. In this study, influential parameters affecting the removal rate of polyethylene microplastics (PEMPs) were optimized through response surface methodology (RSM). In Box Behnken Design (BBD), independent parameters were pH, PEMP size, coagulant dosage and polyacrylamide dosage. Two experimental sets were conducted, one with ferric chloride and the second with poly aluminum chloride as two commonly applied coagulants in drinking water treatment plants (DWTPs). Comparing the results of optimized parameters, PAC was a better coagulant with the predicted removal rate of 58.19%, while the removal rate with ferric chloride as a coagulant was predicted to be 56.37%. Moreover, some experiments were conducted to analyze the effect of ozone gas and sodium hypochlorite as disinfectants on removal rate. The highest removal rate was observed when 2 ppm of O3 was added to the solution coagulated with optimal dosage of PAC, reaching the removal rate of 76.8%. HIGHLIGHTS Use of RSM for MPs removal optimization in coagulation process.; Investigation of disinfectant effects on MPs sinking behavior.; Comparison of two commonly used coagulants in optimization.; Comparison of ozone and chlorine as disinfectants in MPs removal behavior.;